Prevalence of obesity and overweight and factors associated with it among medical students of Bundelkhand region: A cross-sectional study - Ashish Niranjan,; Aditya Pandey,; Vimal Arya,; Nilima Takhelchangbam, (Asian Journal of Medical Sciences, 2023)
Background: Due to their sedentary lifestyle, abnormal eating habits, and increased reading and technology use, our medical students are more likely to be obese. Aims and Objectives: The objective of the study was to estimate the prevalence of overweight and obesity and its association with demographic characteristics, family history, and dietary habits in medical students of our tertiary care teaching institute. Materials and Methods: This institutional-based cross-sectional study comprised 260 medical students from all professional years of the M.B.B.S. course. Weight and height of participating students were recorded. Participants were then categorized based on Asia-Pacific classification of BMI. A pre-designed, pre-tested, semi-structured questionnaire was utilized for obtaining demographic information, dietary habits, and family history of participant. Results were expressed in frequency and percentages, and the Chi-square test was applied to find out the association of dependent variables with overweight and obesity. Results: The majority of study participants were between ages of 18 and 21 (47.69%), males (53.46%) and hostellers (96.15%). The prevalence of overweight and obesity was 22.31% and 23.18%, respectively. Overweight and obesity were significantly associated with a family history of overweight and obesity, eating out frequency, and with the frequency of consumption of fast food and snacks (P=0.001). Conclusion: The prevalence of overweight and obesity among medical students was found to be high in our tertiary care teaching institute located in Central India. This study concludes that behavior change communication programs should be designed to encourage the adoption of healthy habits such as Ashtanga yoga, regular exercise, a balanced diet, and the avoidance of junk foods.